2006
DOI: 10.1139/g06-032
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization and phylogenetic analysis of a novel glutenin gene (Dy10.1t) fromAegilops tauschii

Abstract: A novel y-type high molecular mass glutenin subunit (HMM-GS) possessing a mobility that is slightly slower than that of the subunit Dy10 obtained by SDS-PAGE, named Dy10.1t, in the wild wheat Aegilops tauschii was identified by 1- and 2-dimensional gel electrophoresis, capillary electrophoresis, and matrix-assisted laser desorption ionization time of flight mass spectrometry (MALDI-TOF-MS). The gene encoding the HMM subunit Dy10.1t was amplified with allele-specific PCR primers, and the amplified products were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
18
0
2

Year Published

2007
2007
2011
2011

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 54 publications
1
18
0
2
Order By: Relevance
“…The molecular characteristics of glutenin genes can reveal primary genetic mechanisms for their allelic variations as well as origin and evolution. First, a number of SNP variations resulted from dot mutation in glutenin genes, as shown in this study and recent reports Zhang et al 2006), may lead to nonsynonymous SNP and various amino acid substitutions, resulting in extensive allelic variations among LMW subunits. Second, indels, duplications, and inversions of one and more repeats by un- equal crossing over or slippage (Anderson and Greene 1989) could result in striking expansion or contraction of glutenin genes.…”
Section: Pcr Amplification and Cloning Of Lmw-gs Genesmentioning
confidence: 57%
See 1 more Smart Citation
“…The molecular characteristics of glutenin genes can reveal primary genetic mechanisms for their allelic variations as well as origin and evolution. First, a number of SNP variations resulted from dot mutation in glutenin genes, as shown in this study and recent reports Zhang et al 2006), may lead to nonsynonymous SNP and various amino acid substitutions, resulting in extensive allelic variations among LMW subunits. Second, indels, duplications, and inversions of one and more repeats by un- equal crossing over or slippage (Anderson and Greene 1989) could result in striking expansion or contraction of glutenin genes.…”
Section: Pcr Amplification and Cloning Of Lmw-gs Genesmentioning
confidence: 57%
“…The gene sizes vary, depending mainly on the number of repeats in the repetitive domain, normally ranging from 12 to 25 amino acid residues. The extensive allelic variation among both LMW-GS and HMW-GS genes are due mainly to single nucleotide polymorphisms (SNPs) and insertions/deletions (indels) of repetitive units ( Johal et al 2004;Yan et al 2004;An et al 2006;Zhang et al 2006;Li et al 2008). It was speculated that the genetic mechanisms for these variations may result from unequal crossing over and slippage during replication and dot mutation (Anderson and Greene 1989;D'Ovidio et al 1996;An et al 2006).…”
mentioning
confidence: 99%
“…1Dy10) were used as controls for SDS-PAGE. MALDI-TOF-MS was performed on the AX1MA-CFRTMPlus mass spectrometer (Shimadzu, Japan) and the procedure for measuring the molecular mass of HMW-GSs was carried out as described by Zhang et al (2006).…”
Section: Sds-page and Mass Spectrometrymentioning
confidence: 99%
“…tauschii have been characterized (Wan et al 2005). Evidence from molecular analysis demonstrated that the HMW glutenin subunits from wheat and related species have highly conserved structures, consisting of a signal peptide (21 residues), an N-terminal domain (86-89 residues in x-type and 104 in y-type subunits), a C-terminal domain (42 residues), and a central repetitive domain (630-830 residues) that is mainly responsible for differences in molecular weight of the subunits Wan et al 2002Wan et al , 2005Yan et al 2004;Sun et al 2006;Zhang et al 2006). The HMW glutenin genes, therefore, could derive from a common ancestor.…”
mentioning
confidence: 99%
“…The HMW glutenin genes, therefore, could derive from a common ancestor. The main molecular mechanisms for the evolution of glutenin genes at the Glu-1 loci appear to be single nucleotide polymorphism (SNP) and insertion/deletion (indel) variations, duplications, and deletions of large repeats, probably resulting from events such as unequal crossover and slip-mismatching D'Ovidio et al 1996;Zhang et al 2006).…”
mentioning
confidence: 99%